Radiofrequency Ablation and Microdebrider-Assisted Turbinoplasty: 5-Year Postoperative Outcomes - Shin Hyuk Yoo; Hyo-Yeon Kim; Yoon-Ah Kim; Ji-Hun Mo (Journal of Rhinology, 2023)
Background and Objectives Turbinoplasty may be an option in patients with persistent symptoms of allergic rhinitis (AR) despite adequate medication. The two most frequently used surgical techniques for turbinoplasty are radiofrequency ablation and microdebriderassisted turbinoplasty. This study compared the outcomes of these two surgical techniques and assessed the long-term treatment effects. Methods This study included patients with AR who underwent turbinoplasty between January 2010 and June 2017. We examined the medication scores, overall treatment satisfaction scores, and medical records. Based on the type of surgery, patients were classified into microdebrider and coblator groups. A telephone survey was conducted to collect data on the 5-year post-treatment efficacy parameters. Scores for allergic symptoms, prescription medicines taken after surgery, and general satisfaction were compared. Results Of the total 241 patients, 192 (79.7%) and 49 (20.3%) underwent microdebrider-assisted turbinoplasty and radiofrequency ablation turbinoplasty, respectively. Both the microdebrider and coblator groups showed remarkable improvements in AR symptoms at the 5-year follow-up (p<0.001). Although the degree of symptom improvement did not differ significantly between the two groups, the coblator group did show significant improvements in medication scores when compared with the microdebrider group (p<0.05), and there were significant differences in postoperative satisfaction scores between the two groups. Conclusion In terms of 5-year postoperative outcomes, radiofrequency-ablation turbinoplasty and microdebrider-assisted turbinoplasty were equally beneficial for reducing nasal symptoms and enhancing medication ratings in patients with AR.